Trust as a Mediator of Perceived Ease of Use and Promotion in Shopeepay Transaction Decisions in Banyumas Regency - Aulia Fitria Salmah; Faizal Rizky Yuttama; Puspita Lianti Putri (CV. Era Digital Nusantara, 2026)
The rapid development of digital technology has accelerated the adoption of e-wallets, particularly ShopeePay, as a primary non-cash payment method. This study analyzes the structural relationships between perceived ease of use, promotion, user trust, and transaction decisions among ShopeePay users in Banyumas Regency. Adopting a quantitative survey design, data were collected via structured self-report questionnaires from a purposive sample of 200 active users aged 18–50 years residing in the region. Data were processed using IBM SPSS Statistics 27. In the mediator model (Z =Trust), ease of use (beta = 0.197, p < 0.001) and promotion (beta = 0.563, p < 0.001) significantly predicted user trust, explaining 63.5% of its variance (R2 = 0.635). In the outcome model (Y = Transaction Decision), trust (beta = 0.500, p < 0.001), ease of use (beta = 0.134, p = 0.001), and promotion (beta= 0.286, p < 0.001) exerted significant direct effects, accounting for 63.5% of the total variance (R^2 = 0.635, Adjusted R^2 = 0.630). Path analysis indicated indirect effects of ease of use (ab = 0.150) and promotion (ab = 0.293) on transaction decisions through trust. Although traditional Sobel tests indicated statistical significance (Z = 3.140, p = 0.002 and Z = 6.626, p < 0.001, respectively), these results assume normal sampling distributions and require cautious interpretation due to detected heteroscedasticity in the outcome model (p < 0.05). Assuming non-normal error distribution, bias-corrected bootstrap confidence intervals (95% CI) confirmed that trust serves as a significant partial mediator for both paths. These findings emphasize that user trust, driven by strategic promotions and seamless usability, acts as a primary psychological mechanism in shaping digital transaction behavior. However, the study’s generalizability is constrained by its cross-sectional design, reliance on self-reported perceptual data, non-probability purposive sampling, potential common-method bias, and the absence of actual transaction log data.